2002
DOI: 10.1002/cncr.10601
|View full text |Cite
|
Sign up to set email alerts
|

Psychic vulnerability and the associated risk for cancer

Abstract: BACKGROUND Psychic vulnerability has been associated with a number of physical symptoms and diseases. This study was designed to estimate the incidence of cancer in a random sample of persons in the general Danish population in relation to a personality characteristic measured by the Test of Psychic Vulnerability. METHODS The authors examined the cancer incidence in a cohort of 5136 randomly sampled persons age > 25 years living in Copenhagen County, Denmark. The responses to questionnaires and the results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 24 publications
(28 reference statements)
0
16
1
3
Order By: Relevance
“…9 Thus, the results of well conducted studies in which other measures of personality were used, such as Type A behavior, hostility, and psychic vulnerability, are in line with our current and previous findings that personality traits are not associated with an increased risk for cancer. 9,50 In conclusion, although the causes of some cancers are well established, there remain many cancers for which the risk factors largely are unknown. This leaves room for speculation, including the common belief that the mind may cause certain cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Thus, the results of well conducted studies in which other measures of personality were used, such as Type A behavior, hostility, and psychic vulnerability, are in line with our current and previous findings that personality traits are not associated with an increased risk for cancer. 9,50 In conclusion, although the causes of some cancers are well established, there remain many cancers for which the risk factors largely are unknown. This leaves room for speculation, including the common belief that the mind may cause certain cancers.…”
Section: Discussionmentioning
confidence: 99%
“…No significant effect of psychic vulnerability was found on the risk for cancer (HR, 1.16; 95%CI, 0.85-1.57). 50 Type A behavior, which is defined as time urgency, ambitiousness, competitive drive, and aggressiveness, was studied prospectively among 11,272 women who were followed for breast cancer for 20 years. No significant effect of Type A behavior on the risk for breast cancer was observed (HR, 1.15; 95%CI, 0.73-1.82).…”
Section: Discussionmentioning
confidence: 99%
“…A national Danish study demonstrated that mentally vulnerable persons, compared with nonvulnerable individuals, report more diseases and symptoms, use health services more often, and have a less healthy lifestyle [13]. In other studies, mental vulnerability has been associated with upper dyspepsia [14], irritable bowel syndrome [15], peptic ulcer [16], and early mortality [17], but not with cancer [18]. Furthermore, mental vulnerability predicted persistent pain after lumbar spine surgery [19] and cholecystectomy [20,21], independently of known risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…In the personalityhealth behavior model, personality or psychological factors are assumed to predispose to life style factors that influence cancer risk. 28 The categorization into etiologic groups on the basis of both life style and immunologic and hormonal factors applied in the current analyses fits the assumed mechanisms in both theories.…”
Section: Statistical Analysesmentioning
confidence: 78%